Youth Participatory Action Research and Applied Theatre Engagement: Supporting Indigenous Youth Survivance and Resurgence - Conrad, Diane (Theatre Research in Canada / Recherches théâtrales au Canada)

(untitled) (University of Toronto Press, 2020)
For Indigenous youth in Canada, times are challenging, but the challenges youth face do not define the wholeness of their lived realities. This article focuses on applied theatre engagement, drawing on three youth participatory action research projects with Indigenous youth in three diverse contexts: in a school setting, in a youth offender jail, and with a community-based organization serving street-involved youth. It explores the significance of applied theatre approaches to research with Indigenous youth to avoid reproducing one-dimensional damage-centred narratives in favour of inspiring processes for survivance and resurgence. The discussion emphasizes the ways in which research can offer support for youth to become empowered and for others to see the youths’ wisdom and hope alongside the struggles that together shape their realities.